Smart Parking System Mobile Application using Ultrasonic Detector - A Aziz, Fatin Areena; Mohd Muji, Siti Zarina; Abd Wahab, Mohd Helmy; Tukiran, Zarina; Uttrapan, Chessda; Sudin, Nor'aisah (International Journal of Integrated Engineering, 2022)
Finding an empty parking lot is a big challenge as it can take lots of time and resources. This paper describes the design and development of a prototype of a smart parking system for assisting the vehicle drivers who always experiencing problem in finding indoor parking lots. The objectives of the proposed system are to develop a IoT parking lot system utilizing ultrasonic sensor to detect the presence of a vehicle and to develop a mobile application to display the parking lot layout for assisting car drivers to locate an empty parking lot. For the controller unit, it consists of the Arduino UNO microcontroller which is programmed using JavaScript language. Arduino is used to control the sensor, build a connection with the firebase server and update any changes in the hardware to the firebase. This enables the ultrasonic transmitter and collects the sensing data to be passed to the data transmission and acquisition unit.  Once the ultrasonic sensor detects a car, the signal is read and processed by the microcontroller before it is sent to the server to update the status of the parking availability. The accuracy of vehicle detection is 100% with a standard deviation for sensor A0 and sensor A1 are 0.5 and 0.32 respectively. The display result of the parking lot availability is automatically updated in the mobile phone application in real-time.